The Early Diagnostic Dilemma in Angioimmunoblastic T Cell Lymphoma with Excessive Plasma Cells Proliferation. (16th July 2021) - Wang, Chunyan; Mao, Xia; Liu, Songya; He, Cheng; Wang, Ying; Zhu, Li; Wang, Yangyang; Zhang, Yicheng
Abstract : Background . Angioimmunoblastic T cell lymphoma (AITL) is an aggressive Epstein–Barr virus-associated T cell lymphoma. Clinical syndromes of AITL are not confined to fever and lymphadenopathy, and patients may initially present with polyclonal plasma cell proliferation, which may obscure the underlying disease of AITL, delaying diagnosis. Case Presentation . Here, we report two AITL patients with excessive plasma cell proliferation in the bone marrow, peripheral blood, and ascites even mimicking plasma cell leukemia. Both of them had poor endings. Conclusions . Our report emphasizes the complexity of the clinical manifestations of AITL, which aims to increase the alertness of physicians and improve the rate of early diagnosis. Integrated diagnostic approaches such as histopathology, flow cytometry, cytogenetics, and molecular biology are essential for accurate diagnosis and precise therapy.